Vulnerability of women living with HIV/aids - Marli Teresinha Cassamassimo Duarte; Cristina Maria Garcia de Lima Parada; Lenice do Rosário de Souza (Universidade de São Paulo, 2014)
OBJECTIVE: outline the profile of women living with the human immunodeficiency virus/aids in interior cities in São Paulo State, in the attempt to identify characteristics related to individual, social and programmatic vulnerability and to analyze the conditions in which they discovered their serological status. METHOD: between October 2008 and December 2010, a cross-sectional study was undertaken with 184 women attended at a specialized service. The data were collected through an interview and gynecological test, including the collection of samples for the etiological diagnosis of sexually transmissible conditions. RESULTS: the women were predominantly white, between 30 and 49 years of age, lived with a partner, had a low education level, multiple sexual partners across the lifetime and unsafe sexual practices. The prevalence of sexually transmitted diseases corresponded to 87.0%. CONCLUSION: the study suggests the need to offer gynecological care in specialized services and the accomplishment of multiprofessional actions to reinforce the female autonomy in protective decision making.